Implementation of Islamic Religious Education Integrated with the Qur'an-Based Environment in SD Alam Pacitan - Ridho Riyanto; Waharjani; Rika Astari; Djamaluddin Perawironegoro; Betty Maulirosa Bustam (State Islamic Institute of Madura, 2025)
The research problem originates from the observation that SD Alam Pacitan has experienced a significant decline in the internalization of environmental awareness in recent years. This deterioration is evidenced by increasing ecological crises in Pacitan, including frequent landslides, floods, and seasonal droughts. In response, the school is motivated to integrate ecology-based learning materials into its Islamic Religious Education (IRE) curriculum. Accordingly, this study seeks to examine the development and reinforcement of Qur’anic verses within ecology-oriented IRE, enabling students to comprehend nature through both Islamic and scientific perspectives. Employing a qualitative case study approach, the research involves data collection through interviews, observations, and documentation. Data analysis follows three stages: reduction, display, and conclusion drawing, with triangulation applied to ensure validity. The findings reveal that embedding Qur’anic verses into ecology-based IRE at SD Alam Pacitan enriches the pedagogical experience, fostering a holistic understanding of life by linking ecological themes with Islamic teachings.